Risk Factors for Testing Positive for Severe Acute Respiratory Syndrome Coronavirus 2 in a National United States Healthcare System. (26th October 2020) - Fan, Vincent S; Dominitz, Jason A; Eastment, McKenna C; Locke, Emily R; Green, Pamela; Berry, Kristin; O'Hare, Ann M; Shah, Javeed A; Crothers, Kristina; Ioannou, George N
Abstract: Background: Identifying risk factors for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection could help health systems improve testing and screening strategies. The aim of this study was to identify demographic factors, comorbid conditions, and symptoms independently associated with testing positive for SARS-CoV-2. Methods: This was an observational cross-sectional study at the Veterans Health Administration, including persons tested for SARS-CoV-2 nucleic acid by polymerase chain reaction (PCR) between 28 February and 14 May 2020. Associations between demographic characteristics, diagnosed comorbid conditions, and documented symptoms with testing positive for SARS-CoV-2 were measured. Results: Of 88 747 persons tested, 10 131 (11.4%) were SARS-CoV-2 PCR positive. Positivity was associated with older age (≥80 vs <50 years: adjusted odds ratio [aOR], 2.16 [95% confidence interval CI, 1.97–2.37]), male sex (aOR, 1.45 [95% CI, 1.34–1.57]), regional SARS-CoV-2 burden (≥2000 vs <400 cases/million: aOR, 5.43 [95% CI, 4.97–5.93]), urban residence (aOR, 1.78 [95% CI, 1.70–1.87]), black (aOR, 2.15 [95% CI, 2.05–2.26]) or American Indian/Alaska Native Hawaiian/Pacific Islander (aOR, 1.26 [95% CI, 1.05–1.52]) vs white race, and Hispanic ethnicity (aOR, 1.52 [95% CI, 1.40–1.65]). Obesity and diabetes were the only 2 medical conditions associated with testing positive. Documented fevers, chills, cough, and diarrhea were also associated with testing positive. The population attributable fraction of positive tests was highest for geographic location (35.3%), followed by demographic variables (27.1%), symptoms (12.0%), obesity (10.5%), and diabetes (0.4%). Conclusions: The majority of positive SARS-CoV-2 tests were attributed to geographic location, demographic characteristics, and obesity, with a minor contribution of chronic comorbid conditions. Abstract : A positive SARS-CoV-2 polymerase chain reaction test was associated with older age, male sex, geographic burden of disease, nonwhite race and Hispanic ethnicity, obesity, and diabetes. The majority of positive tests were attributed to geographic burden, demographic characteristics, and obesity.